Socio-Scientific Issues-Based E-Module using Liveworksheets to Enhance Students' Scientific Literacy on Acid-Base Topics - Istikomah Yulfa Agustin; Jamil Suprihatiningrum; Agus Kamaludin; Dewi Vitama Pusfitasari (Yayasan Keluarga Guru Mandiri, 2025)
According to PISA data, the level of scientific literacy in Indonesia is relatively low, highlighting the need for innovative learning media tailored to the needs of Generation Z students. This study aims to develop an e-module based on socio-scientific issues using the Liveworksheets platform to enhance students' scientific literacy on acid-base topics. The research employed a Research and Development (RD) method with the ADDIE model, encompassing analysis, design, and development phases. Product validation was conducted by material experts, media experts, and reviewers, while a limited trial was carried out with students. Validation results revealed that the e-module achieved an excellent category from material experts, media experts, and reviewers, with an average ideality percentage of 95%. Student trials also yielded positive responses with excellent content, language, and user-friendliness ratings. The developed e-module incorporates relevant socio-scientific issues, supports technology-based learning, and is designed to accommodate visual, auditory, and kinesthetic learning styles. Therefore, this e-module is an innovative and effective alternative learning medium to improve students' scientific literacy on acid-base topics. In addition, this e-module has the potential to nurture scientifically literate citizens who can contribute to solving socio-scientific issues in society.